The practicality of practice: A model of the function of play behaviour - Mallpress, Dave E W; Špinka, Marek (Ecology and evolution, 2023)
The function of play has been a long-debated topic in animal behaviour. One popular class of accounts is that play offers practice for serious adult behaviour, but little has been done to model the circumstances where this could be true. In this paper, we model an individual who, over the juvenile and subadult ontogenetic periods, has a choice between three behaviours: foraging, playing and rest, where playing improves an individual's ability in some component of a serious adult behaviour. Using stochastic dynamic programming, we show that even when play is more energetically costly and an inferior form of practice than foraging itself, it still may be optimal to play under a variety of circumstances. We offer several instantiations of the play as practice concept to show the possibility of play improving a variety of different adult abilities: antipredatory, foraging and reproductive behaviour. These models show the environmental conditions where play might be expected, as well as the predicted occurrences of play throughout ontogeny. This is a first step in showing the ecological feasibility of the practice hypothesis of play and raises further questions about why playful activity is more beneficial than more deliberate directed practice.
Keywords: dynamic programming; modelling; play behaviour; practice hypothesis